Chapter The 'Second Level' Education Professional: a Traineeship Programme Fostering a Proactive Approach to Employability - Palmieri, Cristina (Studies on Adult Learning and Education, 2018)
In this chapter, we outline the process that led to the development of the current traineeship programme − Tirocinio Formativo e di Orientamento (TFO) related to the Master's Degree Course in Education at the University of Milan-Bicocca. We focus particularly on the interconnection between developing professional competences and addressing the issue of employability